If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x-12=3x+3=
We move all terms to the left:
6x-12-(3x+3)=0
We get rid of parentheses
6x-3x-3-12=0
We add all the numbers together, and all the variables
3x-15=0
We move all terms containing x to the left, all other terms to the right
3x=15
x=15/3
x=5
| -8d+9=-d-1-8d | | -12b+11=13b-7 | | a=5=18 | | -6.1t+14.12+10.55=-16.27-8.4t | | -d-20=-4d+d+20 | | -19-17n=17-20n | | 3h=-9h-12 | | 9k-3=7k+1 | | -2x=104 | | (3y-8)=56 | | -2j+6=-3+8-3j | | 5*x+2*x=820 | | -3-5m=-6m-1 | | -8+6(y-6)=-38 | | 250000(1+r)^10=447711.92 | | 5x+2x=820 | | 6z=5z-10 | | (x+30)=(9x+6) | | 12x+44=188 | | -1+8h=7h-10 | | 9x+5=37 | | (2x-2)+(3x+12)=90 | | 4-8f=6f+4 | | (x+17)+(x-5)=180 | | -2-9z=-10z | | 12x=191 | | 22+3x=34 | | 167=c200 | | 6x-55=5 | | 8(-2m+2)=8m-392 | | 14x^2+70x-336=7x^2+14x-105 | | 12=t+10 |